Metal–Insulator Transition Driven by Traps in 2D WSe2 Field‐Effect Transistor. (29th March 2022) - Ali, Fida; Ali, Nasir; Taqi, Muhammad; Ngo, Tien Dat; Lee, Myeongjin; Choi, Hyungyu; Park, Won‐Kyu; Hwang, Euyheon; Yoo, Won Jong
Abstract: Localized trap density ( D t ) at the 2D channel–gate dielectric interface and its relative strength to carrier–carrier interactions depending on the thickness of the 2D channel can determine the nature of a metal–insulator transition (MIT) in 2D materials. Here, the MIT occurring in WSe2 devices is systematically analyzed by varying the WSe2 thickness from ≈20 nm to monolayer to explore the effects of D t on MIT. The corresponding critical carrier density increases from ≈8.30 × 10 11 to 9.45 × 10 12 cm –2 and D t from ≈6.02 × 10 11 to 1.13 × 10 13 cm –2 eV –1 as WSe2 thickness decreases from ≈20 nm to monolayer. These large increments in D t with decreasing thickness of WSe2 induce a strong potential fluctuation in the band of WSe2, causing charge density inhomogeneity in the system, which attributed to tuning the MIT. The critical percolation exponent is strongly dependent on WSe2 thickness with an excellent agreement between the transport data and percolation theory achieved from thinner WSe2 devices, while the transport data measured from multilayer WSe2 devices does not obey the percolation theory. These results suggest that the nature of MIT strongly depends on the WSe2 channel thickness and corresponding unscreened charge impurity and strength of D t at the interface. Abstract : It is observed that the metal–insulator transition in 2D‐WSe2 devices is strongly dependent on channel thickness and localized trap density ( D t ) at the WSe2 /hBN interface. The estimated critical carrier density at the transition point significantly increases with the decreasing thickness of WSe2, attributed to dramatically increased localized D t in thinner devices.